Flexible fibre optic vs digital ureteroscopy and enhanced vs unenhanced imaging for diagnosis and treatment of upper tract urothelial carcinoma (UTUC): results from the Clinical Research Office of the Endourology Society (CROES)‐UTUC registry. (13th June 2021) - Soria, Francesco; Laguna, M. Pilar; Roupret, Morgan; Garcia‐Marchinena, Patricio; Gonzalez, Mariano Sebastián; Habuchi, Tomonori; Erkan, Erkan; Ng, Anthony; Gontero, Paolo; de la Rosette, Jean
Abstract : Objectives: To compare the oncological outcomes of patients with upper tract urothelial carcinoma (UTUC) undergoing kidney‐sparing surgery (KSS) with fibre‐optic (FO) vs digital (D) ureteroscopy (URS). To evaluate the oncological impact of image‐enhancement technologies such as narrow‐band imaging (NBI) and Image1‐S in patients with UTUC. Patients and Methods: The Clinical Research Office of the Endourology Society (CROES)‐UTUC registry is an international, multicentre, cohort study prospectively collecting data on patients with UTUC. Patients undergoing flexible FO‐ or D‐URS for diagnostic or diagnostic and treatment purposes were included. Differences between groups in terms of overall survival (OS) and disease‐free survival (DFS) were evaluated. Results: The CROES registry included 2380 patients from 101 centres and 37 countries, of whom 401 patients underwent URS (FO‐URS 186 and D‐URS 215). FO‐URS were performed more frequently for diagnostic purposes, while D‐URS was peformed when a combined diagnostic and treatment strategy was planned. Intra‐ and postoperative complications did not differ between the groups. The 5‐year OS and DFS rates were 91.5% and 66.4%, respectively. The mean OS was 42 months for patients receiving FO‐URS and 39 months for those undergoing D‐URS ( P = 0.9); the mean DFS was 28 months in the FO‐URS group and 21 months in the D‐URS group ( P < 0.001). In patients who received URS with treatment purposes, there were no differences in OS ( P = 0.9) and DFS ( P = 0.7). NBI and Image1‐S technologies did not improve OS or DFS over D‐URS. Conclusions: D‐URS did not provide any oncological advantage over FO‐URS. Similarly, no differences in terms of OS and DFS were found when image‐enhancement technologies were compared to D‐URS. These findings underline the importance of surgeon skills and experience, and reinforce the need for the centralisation of UTUC care.